Developing a comprehensive, culturally sensitive conceptual framework of health domains in Singapore. - Julian Thumboo; Mandy Y L Ow; Elenore Judy B Uy; Xiaohui Xin; Zi Ying Clarice Chan; Sharon C Sung; Dianne Carrol Bautista; Yin Bun Cheung (PLoS ONE, 2018)
The increasing focus of healthcare systems worldwide on long-term care highlights the need for culturally sensitive Health-Related Quality of Life instruments to accurately capture perceived health of various populations. Such instruments require a contextualized conceptual framework of health domains, which is lacking in some socio-cultural contexts. We developed a comprehensive and culturally sensitive conceptual framework of health domains relevant to the Singaporean population. We recruited Singaporeans/ permanent residents, English/ Chinese-speaking, with/ without chronic illnesses to participate in focus group discussions (FGDs) and in-depth interviews (IDIs). We elicited health areas participants perceived to be important for them to be happy and satisfied with life. To encourage spontaneous emergence of themes, we did not specify any aspect beyond the broad domains of Physical, Mental, and Social health so as not to limit the emergence of new themes. Themes from the transcripts were distilled through open coding (two independent coders), then classified into more abstract domains (each transcript coded independently by two coders from a pool of six coders). From October 2013 to August 2014, 121 members of the general public participated in 18 FGDs and 13 IDIs (44.6% males, mean age: 53.3 years 77% Chinese, 9% Malay, 12% Indian, 63% with chronic illness) while 13 healthcare workers participated as patient-proxies in three FGDs. Thematic analysis identified 27 domains. The 15 physical domains included physical appearance, energy, physical fitness, and health and resistance to illness. The nine mental domains included emotions, self-esteem, and personal freedom. The three social domains were social contact, social relationships, and social roles. This conceptual framework reflected physical, mental, and social dimensions of well-being, suggesting that the Singapore population's views on health support the World Health Organization's definition of health as "a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity".